The relationship between pedal force application technique and the ability to perform supramaximal pedaling cadences - Yamaguchi, Yuta; Otsuka, Mitsuo; Watanabe, Kohei; Wada, Naoki; Nishiyama, Tetsunari (Frontiers in Sports and Active Living, 2022)
This study aimed to examine the relationship between the pedal force application technique under a specific competitive condition and the ability to perform steady-state pedaling at a supramaximal cadence during a special pedaling test. A total of 15 competitive male cyclists and 13 active, healthy men (novice cyclists, hereafter, novices) performed the pedaling technique test. The test imitated a road cycling competition condition (80% VO2 peak and a cadence of 90 rpm). Additionally, they performed a supramaximal cadence test that evaluated the ability to perform steady-state pedaling for an ultra-high cadence (range of 160–220 rpm) of 30 s stably with a 0.1 kgf. For the pedaling technique test, kinetic data were obtained by the pedal-shaped force platform at 1,000 Hz, and the pedaling technique was determined by the index of force effectiveness (IFE). For the supramaximal cadence test, kinematic data were obtained using a motion capture system at 200 Hz. The supramaximal pedaling cadence (Cmax) was determined by measuring exercise time and targeted pedaling cadence. The IFE was 48.0 ± 9.7% in cyclists and 32.0 ± 5.9% in novices. The Cmax was 215.5 ± 8.8 rpm in cyclists and 192.2 ± 13.0 rpm in novices. These values were significantly higher for cyclists than for novices. Cmax was moderately correlated with IFE (r = 0.64). No significant correlation was observed between Cmax and IFE for cyclists only; in contrast, a moderate correlation was observed between these parameters for novices only (r = 0.67). In conclusion, the pedal force application technique under a specific competitive condition is related to the ability to perform steady-state pedaling for supramaximal cadence during the test. Therefore, Cmax may be able to explain pedal force application techniques without the need for expensive devices for novices.